KNOWLEDGE, ATTITUDE AND USE OF ALTERNATIVE MEDICAL THERAPY AMONGST URBAN RESIDENTS OF OSUN STATE, SOUTHWESTERN NIGERIA - Bamidele, J. O.; Adebimpe, W. O.; Oladele, E. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Alternate medicine which has a long history has been relegated to the background by the evolution of modern medicine. In recent times, however, alternative medical therapy has been growing in popularity and getting increasing attention and interest. This study assessed the knowledge, attitude and use by urban dwellers of alternative medical therapies. This was a cross-sectional descriptive study which used a semi-structured questionnaire to gather information from 812 randomly selected urban respondents. Majority 734 (90.4%) of the respondents were aware of an alternative way of getting treatment for their ailments apart from the orthodox medicine. The forms of alternative medical therapy (AMT) respondents were aware of include: concoction (herbal preparations) 683 (94.2%); herbalists/traditionalists 616 (85.0%); traditional bone setters therapy 434 (59.9%); among others. The main source of information was through radio 439 (70.9%). About half 403 (54.9%) of the respondents were aware of side effects from AMT and these include diarrhea, abdominal pain and vomiting which accounts for 69.7%; 42.2% and 40.2% respectively. About 347 (47.3%) think AMT could be injurious to health. About a third 262 (35.7%) of the respondents who were aware of AMT prefers it to orthodox medicine. Reasons given for the preference were that: AMT is cheap 56 (21.4%); accessible 43 (16.4%) and acceptable 35 (13.4%) to them. About half 367 (50.0%) also believed AMT alone could cure their illness without resort to orthodox medical therapy (OMT). Over half 401 (54.6%) of the 734 respondents that were aware of AMT had patronized or taken one form of alternative medical therapy or the other in the last 12 months prior to the study. Of these number, 323 (80.5%) had taken concoction (herbal preparations). However, there was no relationship between respondents’ age, sex, educational level or religion and the patronage of AMT as all test of associations were not statistically significant p>0.05. This study has revealed that the use of alternative medical therapies is quite popular among the studied population and a high proportion of the respondents use AMT notwithstanding that they live in the urban communities where they have better access to orthodox medical care and medical practitioners. Regulations should be made concerning the advertisement of alternative medicine and practices as orthodox medicine and practices are usually not advertised